Exploring mathematical technological knowledge of teachers with Geogebra application - Ma'rufi, Ma'rufi; Ilyas, Muhammad; Ikram, Muhammad; Seti, Sirikanya (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Geogebra is a mathematical software that can be used in mathematics, especially geometry, calculus, and dynamic algebra, with various features, especially visualization. Geogebra helps students identify and improve their visual skills in understanding mathematical concepts. This study aims to explore the mathematical technology knowledge of teachers based on Geo-Gebra applications in mathematics learning by integrating content and technology. This research is qualitative research that uses a single-case design to explore the teacher's mathematical technology knowledge and involved teachers (N = 8) from the field of mathematics at universities in the Central Region of Indonesia. Three types of data were collected during one semester, weekly observations, progress report description; and the developed learning design. This research shows that there are two categories of teachers' mathematical technology knowledge characteristics. First, moderate teachers produce simple designs and are still influ-enced by numerical and algebraic approaches. Second, expert teachers can use analytical skills to design step-by-step learning, involving animation to explain concepts, and the resulting designs are quite complex and structured. These two findings are useful for building teacher competencies regarding using GeoGebra ap-plication-based technology in learning mathematics.